2018
DOI: 10.1186/s12881-018-0660-3
|View full text |Cite
|
Sign up to set email alerts
|

High genetic carrier frequency of Wilson’s disease in France: discrepancies with clinical prevalence

Abstract: BackgroundWilson’s disease (WD) is a rare autosomal recessive metabolic disease caused by ATP7B gene mutations tat cause excessively high copper levels, particularly in the liver and brain. The WD phenotype varies in terms of its clinical presentation and intensity. Diagnosing this metabolic disorder is important as a lifelong treatment, based on the use of copper chelating agents or zinc salts, is more effective if it’s started early. Worldwide prevalence of WD is variable, with an average of 1/30,000. In Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
4
47
0
3
Order By: Relevance
“…The larger studies clearly suggest that there are still a number of undiagnosed cases. This is supported by prevalence differences among geographical areas and age groups in the French study, the sex differences in the Taiwan study, and the increase of prevalence estimates with time in the Hong Kong study . Another factor affecting clinical prevalence is potential masking as other diseases, e.g., nonalcoholic steatohepatitis or dementia.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The larger studies clearly suggest that there are still a number of undiagnosed cases. This is supported by prevalence differences among geographical areas and age groups in the French study, the sex differences in the Taiwan study, and the increase of prevalence estimates with time in the Hong Kong study . Another factor affecting clinical prevalence is potential masking as other diseases, e.g., nonalcoholic steatohepatitis or dementia.…”
Section: Discussionmentioning
confidence: 85%
“…In a recent French study, ATP7B DNA was sequenced in 697 patients with diseases other than hepatic and neurologic and without a family history of WD. Among the 1,394 alleles examined, they identified 15 alleles that have been classified as pathogenic, 7 “likely pathogenic” alleles, and 15 alleles with “variants of uncertain significance.” The “likely pathogenic” variants had never been identified in patients with WD, but computer analysis predicted them to be deleterious for protein function.…”
Section: Resultsmentioning
confidence: 99%
“…7 Reports on the prevalence of WD are inconsistent depending on the region of the world and the methods used to diagnose or screen for WD. 10 Furthermore, another study 11 in France showed a high heterozygous carrier frequency of ATP7B yielding a prevalence of 1:31 subjects. By sequencing the entire coding region and adjacent splice sites of ATP7B in 1000 control subjects in the UK, the frequency of carriers with two pathogenic ATP7B mutations was estimated to be of 1 in 7026.…”
Section: Introductionmentioning
confidence: 98%
“…By sequencing the entire coding region and adjacent splice sites of ATP7B in 1000 control subjects in the UK, the frequency of carriers with two pathogenic ATP7B mutations was estimated to be of 1 in 7026. 10 Furthermore, another study 11 in France showed a high heterozygous carrier frequency of ATP7B yielding a prevalence of 1:31 subjects. The authors explained this discrepancy partly due to the clinical variability of WD with incomplete penetrance and existence of modifier genes.…”
Section: Introductionmentioning
confidence: 98%
“…25 Prevalence approaches 1:30,000 in some countries where diagnostic awareness of WD is high, such as Austria 26 and France 27 . However, recent population-genetic studies based on the computer analysis of observed variants have led to estimates of WD prevalence of 1:1,400 28 , 1:7,100 29 or 1:6,500 30 . If true, these studies suggest that at least 75% of people affected by the disease are undiagnosed with potentially fatal consequences.…”
Section: Introductionmentioning
confidence: 99%